Tablet-based Hearing Screening in Children Aged 5 to 17 in Rural Dominican Republic. Issue 7 (August 2018) - Levy, Dylan A.; Hill, David R.; Bia, Frank J.; Feinn, Richard S.
Abstract : Objective: The principal aim of this study was to examine the feasibility of hearing screening using tablet audiometry among a cohort of school-aged children in rural Dominican Republic. The authors hypothesized that the tablet audiometer would serve as an expeditious means for hearing loss screening in various remote locations. Study Design: Cross-sectional. Setting: Twenty-three remote locations in and around the city of La Romana, Dominican Republic. The quietest location available in each site was used for testing. Patients: Inclusion criteria comprised children aged 5 to 17 currently residing in the testing location. Children aged <5 years or >18 years were excluded. Intervention: Screening. Main Outcome Measures: For each subject, air conduction thresholds were obtained bilaterally at 500, 1000, 2000, and 4000 Hz; testing duration was also measured. Hearing loss was suspected if any threshold measured ≥30 dB. Results: In this cohort of 423 subjects, 44 (10.4%) failed the screening protocol. The mean thresholds for 500, 1000, 2000, and 4000 Hz frequencies were 26.05, 22.73, 17.57, and 17.15 dB, respectively. Of the 658 thresholds obtained at ≥30 dB, the majority were at 500 or 1000 Hz. The mean testing duration was 494 seconds. Conclusions: These results suggest that children living in remote communities can be screened quickly for hearing loss using a tablet audiometer. However, significant background noise during testing negatively impacted the low-frequency measurements, thus compromising test reliability. Despite extending the reach of existing audiological services, the value of tablet audiometry is not entirely clear in rural environments with uncontrollable background noise.